A Novel biodegradable system based on poly (lactic‐co‐glycolic acid) nanoparticles for delivery of a novel anticancer peptide - Ahmed M Faheem; Amal Ali Elkordy; Mohamed ElTanani; Samuel M Girgis (University of Huddersfield Press, 2019)
The main objective of this work was to formulate novel amphiphilic PLGA nanoparticles with improved physicochemical properties for the delivery of the novel peptide (CK-10) to be used for targeting of the cancerous/tumour tissue. This was achieved by blending of various amphiphilic polymers with PLGA, especially by using a novel microfluidic technique which can overcome several problems of the conventional techniques like the double emulsion technique e.g. low peptide loading efficiencies, large sizes, and high PDI. Loading efficiency was measured by modified Lowry assay; size and zeta potential were characterized by dynamic light scattering and tuneable pore resistive sensing techniques; images were scanned by scanning and transmission electron microscopes; stability and interaction were confirmed by HPLC-MS, FTIR, DSC and CZE. PLGA/Poloxamer nanoparticles exhibited higher peptide loading than the other types of PLGA nanoparticles [56.13 %m/m for the novel microfluidic technique]. PLGA/Poloxamer prepared by the microfluidics technique had the smallest size with the lowest PDI (208.90 nm, 0.11) which is a vital parameter for targeting. The successful development of better physicochemical properties for the CK-10 loaded PLGA nanoparticles can improve the RAN blocking by CK-10.